Gereja dan Negara: Refleksi atas Tantangan Masyarakat Indonesia dan Pancasila: Suatu Pendekatan Sosiologis - Francisia SSE Seda (Jurnal Orientasi Baru, 2013)
Pancasila is basic for the life of the nation and society in Indonesia. The Church as an element in the Indonesian society has a specific contribution in this civic life. This contribution could not be separated from new relationship between the elements of society-state-market. This new relationship is coloured by the dynamic of societal life after 1998, the new cultural bond, problems of poverty, environment damage and ongoing development. The Churchs contribution could be enlightement in various levels of societal life, such as, guide for social conduct, network creation, development that respons the peoples need, development of the elements of society that is characterized by multiculturalism to achieve a just, prosper, and peaceful society.